Metaphorical modelling of the BRICS image in Russian-language publicist discourse - Irina Y. Parulina (Russian Language Studies, 2025)
The relevance of the study is conditioned by the importance of studying the BRICS image in the discourse of Russia as its key partner. The study shows the perception of the alliance, its mission, and international significance in Russian society, characterizes Russia’s position on global issues and its relations with other BRICS countries. The aim of the study is to identify the dominant metaphorical models creating the BRICS image in Russian-language publicist discourse. The following methods and techniques are used: automated and manual sampling, corpus analysis, metaphorical modelling, and cognitive discourse analysis. Russian National Corpus served as the material. The research text corpus consisted of 500 full-text articles in influential Russian news editions of 2014-2024, and 789 contexts with a metaphorical component were extracted. The study shows that the most frequent metaphorical models are represented by metaphors from the source spheres ‘path’, ‘war’, ‘physics’, and ‘mechanism’. The units of these models characterize the alliance as a sustainable development trajectory to mission implementation and the partner countries as allies in the struggle for a multipolar world. The metaphors from dominant source-sphere reflect the volatile political and economic environment where the BRICS is developing, as well as Western countries’ attempts to put pressure on the alliance’s partner countries. Less common metaphorical models such as living organism, geography, plants, and construction, describe BRICS as a viable association that is ready and able to initiate a transition to a multipolar power balance. The study can become a basis for further research on the BRICS image in the publicist discourse of other countries, as well as in other types of discourse.